Serum Metabolic Profiling of Late-Pregnant Women With Antenatal Depressive Symptoms - Mao, Qiang; Tian, Tian; Chen, Jing; Guo, Xunyi; Zhang, Xueli; Zou, Tao (Frontiers in Psychiatry, 2021)
Background: Antenatal depression is a major public health issue worldwide and lacks objective laboratory-based tests to support its diagnosis. Recently, small metabolic molecules have been found to play a vital role in interpreting the pathogenesis of antenatal depression. Thus, non-target metabolomics was conducted in serum. Methods: Liquid chromatography-mass spectrometry (LC-MS/MS) based metabolomics platforms were used to conduct serum metabolic profiling of antenatal depression (AD) and non-antenatal depression (NAD). Orthogonal partial least squares discriminant analysis (OPLS-DA), the nonparametric Mann–Whitney U-test and Benjamini-Hochberg correction was used to identify the differential metabolites between AD and NAD groups; Spearman’s correlation between the key differential metabolites and Edinburgh Postnatal Depression Scale (EPDS), and the step-wise logistic regression analysis was used to identify potential biomarkers. Results: Totally, 79 significant differential metabolites between AD and NAD were identified. These metabolites mainly influence amino acid metabolism and glycerophospholipid metabolism. Then, PC (16:0/16:0) and betaine were significantly positively correlated with EPDS. The simplified biomarker panel consisting of these three metabolites (betaine, PC (16:0/16:0) and succinic acid) have excellent diagnostic performance (95% CI = 0.911-1.000, specificity = 95%, sensitivity = 85%) in discriminating AD and NAD. Conclusion: The results suggested that betaine, PC (16:0/16:0), and succinic acid were potential biomarker panels, which significantly correlated with depression; and it could make for developing an objective method in future to diagnose AD.